2’-Hydroxy-4’-Ethoxy-4-Methoxychalcone Oxime as an Analytical Reagent for Copper - Desai, J.J.; Desai, P.G.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
In the present work, the authors describes 2´-hydroxy-4´-ethoxy-4-methoxychalcone oxime (HEMCOX) as a gravimetric and spectrophotometric reagent for copper.